Analisis Implementasi Manajemen Kepemimpinan Pendidikan Anak Usia Dini di Taman Kanak-Kanak Kabupaten Cikarang Selatan - Arinda Citra Damareta; Sri Padmantyo (Peneliti.net, 2023)
This study aims to analyze the effect of compensation and organizational support on employee retention, and to determine whether there is a spesific or significant effect of each variable. The research method used in this study is a quantitative method. The population used in this study were employees of PT. Rachma Sari Group with a total sample of 100 respondents. Data were analyzed using regression which was calculated using IBM SPSS Statistics. The results showed that: there is an effect of compensation and organizational support on employee retention. Companies need to prioritize managerial policies in the form of proper, appropriate and fair compensation for their employees to increase employee retention, considering that the compensation variable has a greater calculation result than the organizational support variable